Contextualization of Mathematics Learning Through Decision-Making Schemes in Disaster Mitigation - Al Hasani, Salma Zahrotun Nihayah; Salsabela, Qothrun Nada; Ilmiyah, Nur Fadilatul (Proceeding International Conference on Education, 2024)
The internalization of abstract mathematical concepts often poses a significant challenge for students, even though mathematics is fundamental to numerous disciplines, such as complex decision-making. This study aims to show the critical role of the matrix in the Multi-Attribute Utility Theory (MAUT) method in determining the location of suitable shelters for victims of natural disasters, especially the eruption of Mount Kelud in the Kediri area. This study employs a qualitative descriptive approach to examine the application of the matrix in evaluating various criteria, including the number of public facilities, capacity, availability of bathrooms and ventilation. The study results show that the MAUT method, with the help of a matrix, can provide recommendations for the five most suitable sub-districts as shelter locations. This research is expected to contribute to developing decision support systems for disaster mitigation and improve students' understanding of mathematics applications in real contexts.